1999
DOI: 10.1152/ajpcell.1999.277.2.c225
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in troponin T by a splice donor site mutation that causes hypertrophic cardiomyopathy

Abstract: A splice donor site mutation in intron 15 of the cardiac troponin T (TnT) gene has been shown to cause familial hypertrophic cardiomyopathy (HCM). In this study, two truncated human cardiac TnTs expected to be produced by this mutation were expressed in Escherichia coli and partially (50–55%) exchanged into rabbit permeabilized cardiac muscle fibers. The fibers into which a short truncated TnT, which lacked the COOH-terminal 21 amino acids because of the replacement of 28 amino acids with 7 novel residues, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…skinned cardiac muscle fibers before and after exchanging native cTnT with recombinant human wild-type or ⌬K210 cTnT. Treatment of skinned fibers with an excess amount of recombinant human cTnT resulted in a decrease in the amount of endogenous cTnI and cTnC (lanes 3 and 4) because of displacement of the Tn complex with recombinant human cTnT, as demonstrated in our previous studies (10,14,(30)(31)(32). Subsequent incubation with rabbit cTnI and cTnC accomplished the exchange of recombinant human cTnT into rabbit cardiac muscle fibers (lanes 5 and 6).…”
Section: Preparation Of Skinned Fibers and Force Measurementssupporting
confidence: 70%
See 3 more Smart Citations
“…skinned cardiac muscle fibers before and after exchanging native cTnT with recombinant human wild-type or ⌬K210 cTnT. Treatment of skinned fibers with an excess amount of recombinant human cTnT resulted in a decrease in the amount of endogenous cTnI and cTnC (lanes 3 and 4) because of displacement of the Tn complex with recombinant human cTnT, as demonstrated in our previous studies (10,14,(30)(31)(32). Subsequent incubation with rabbit cTnI and cTnC accomplished the exchange of recombinant human cTnT into rabbit cardiac muscle fibers (lanes 5 and 6).…”
Section: Preparation Of Skinned Fibers and Force Measurementssupporting
confidence: 70%
“…The decrease in Ca 2ϩ sensitivity of force generation also is expected to facilitate the relaxation of the cardiac muscle at diastole and might directly explain the cardiac dilation itself to some extent. In contrast, we have previously shown that the mutations in cTnT associated with HCM have Ca 2ϩ -sensitizing effects on force generation in cardiac muscle (10)(11)(12)(13)(14)(15). The increase in Ca 2ϩ sensitivity of force generation is expected to impair the relaxation of cardiac muscle and thus cause a diastolic dysfunction, which might be directly involved in the high incidence of sudden death despite mild or no hypertrophy in HCM patients associated with cTnT mutations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been shown that the mutations in cTnI associated with HCM modify the effect of cTnI phosphorylation by PKA. Deng et al have shown that R145Q mutation increases the Ca 2+ sensitivity of myosin subfragment-1 ATPase activity and the in vitro filament motility independently of the phosphorylation state of cTnI [79], suggesting that this mutation impairs the mechanism involving cardioprotection through the phosphorylation of cTnI, as with a cTnT mutation [80]. The same group has also reported that the C-terminal mutation K206Q abolishes the sensitivity of myofilaments to the phosphorylation of cTnI by PKA [81].…”
Section: Tni Mutationsmentioning
confidence: 99%